2009
DOI: 10.1111/j.1937-5956.2009.01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Strategies for Perishable Products: The Case of Fresh Produce

Abstract: This paper examines supply chain design strategies for a specific type of perishable product—fresh produce—using melons and sweet corn as examples. Melons and other types of produce reach their peak value at the time of harvest; product value deteriorates exponentially post‐harvest until the product is cooled to dampen the deterioration. Using the product's marginal value of time (MVT), the rate at which the product loses value over time in the supply chain, we show that the appropriate model to minimize lost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
215
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(217 citation statements)
references
References 18 publications
1
215
0
1
Order By: Relevance
“…Empirical studies have found that consumers are sensitive to the freshness of perishable food and usually give a lower valuation to expiring food [28]. Therefore, previous studies dealing with the deterioration of product quality over time have usually assumed quality dependent demand [29,30]. Food safety is a factor that is different from food quality and is difficult to observe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Empirical studies have found that consumers are sensitive to the freshness of perishable food and usually give a lower valuation to expiring food [28]. Therefore, previous studies dealing with the deterioration of product quality over time have usually assumed quality dependent demand [29,30]. Food safety is a factor that is different from food quality and is difficult to observe.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A range of studies on inventory management in retail have been carried out, taking into account different aspects (e.g., see [2][3][4][5]). …”
Section: Literary Reviewmentioning
confidence: 99%
“…It follows that the amount of replenished goods at time t equals the order made at the preceding time. Equation (2) can be applied to a situation in which the amount of replenished goods equals the amount of goods ordered at time t − τ :…”
Section: An Equation Of Inventory Balancementioning
confidence: 99%
“…They used both linear and exponential penalty cost charged for every perishable item held in storage as the usability of the products decayed over time. Recently, Blackburn and Scudder [17] developed a supply chain strategy for perishable products by considering fresh produce value decrease through a supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%